Is Urbanization in Sub-Saharan Africa Different? - Henderson, J. Vernon; Roberts, Mark; Storeygard, Adam (World Bank, Washington, DC, 2013)
In the past dozen years, a literature has developed arguing that urbanization has unfolded differently in post-independence Sub-Saharan Africa than in the rest of the developing world, with implications for African economic growth overall. While African countries are more urbanized than other countries at comparable levels of income, it is well-recognized that total and sector gross domestic product data are of very low quality, especially in Africa. When instead viewed from the perspective of effective technology, as suggested in endogenous growth frameworks (and as proxied by educational attainment), the African urbanization experience overall matches global patterns. There are differences, however, at the sector level. Agricultural trade effects that improve farm prices deter African urbanization, while they promote urbanization elsewhere. Potential reasons include differences in land ownership institutions and the likelihood of agricultural surpluses being invested in urban production. Positive shocks to modern manufacturing spur urbanization in the rest of the developing world, but effects are dependent on the level of development. Thus many countries in Africa, with their lower level of development, do not respond to these shocks. Finally, historical indicators of the potential for good institutions promote urbanization both inside and outside Africa.